Implementation of Restorative Justice in Handling Criminal Acts of Theft in Indonesia - Andhika Damascena, Muhammad Reza; Wahyuningsih, Sri Endah (UNISSULA Semarang, 2025)
Theft is one of the actions or deeds that are against the law. In the Criminal Code, theft can be subject to Article 362. The purpose of the research in this study: 1). To study and analyze the implementation of restorative justice in handling criminal acts of theft in Indonesia; 2). To study and analyze the obstacles and solutions to the implementation of restorative justice in handling criminal acts of theft in Indonesia. This study uses a sociological juridical approach, with a descriptive analytical research method. The data used are primary and secondary data which will be analyzed qualitatively. The research problems are analyzed using the theory of restorative justice and the theory of the legal system of Lawrence Friedman. The results of the study concluded that: 1) The implementation of restorative justice for the crime of theft has begun to be maximized since the issuance of the Circular of the Chief of Police Number SE/2/II/2021 on February 19, 2021 and the Regulation of the Republic of Indonesia National Police Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice issued on August 20, 2021; 2). The application of restorative justice as an alternative to resolving petty theft cases still has several obstacles or weaknesses. The weakness in the legal substance aspect is the time limit stipulated in Article 9 paragraph (5) of the Prosecutor's Regulation No. 15 of 2020, which stipulates a deadline of 14 days from the submission of the file. The weakness in the legal structure aspect is the lack of understanding of law enforcement officers regarding the implementation of resolving the crime of theft with restorative justice. The weakness of the legal culture of the application of Restorative Justice is that not all people are aware of the concept of Restorative Justice as a replacement for the general criminal system. The solution to the weakness of the legal substance aspect is that it is necessary to review the regulations governing the time limit in the Prosecutor's Regulation No. 15 of 2020, with the aim of adding time so that the resolution of cases is not rushed. The solution to the weakness of the legal structure aspect is the need to improve the quality of personnel by providing further education to law enforcers in handling restorative justice cases by improving the quality of personnel, it will also improve the abilities of members, especially restorative justice cases. The solution to the weakness of the legal culture aspect is that the government is advised to re-socialize the implementation of Restorative Justice as an initial step that should be taken in implementing law enforcement in the community.